Access to and demand for online school education during the COVID-19 pandemic in Japan. (January 2023) - Akabayashi, Hideo; Taguchi, Shimpei; Zvedelikova, Mirka
Abstract: The COVID-19 pandemic resulted in school closures worldwide, including in Japan, where remote education at schools is underdeveloped. Using a unique panel dataset collected in May and December 2020, we examine the determinants of access to online education at and outside schools and parents' preference towards at-school online education. We observe that children from more privileged family backgrounds received more at-school as well as outside-school online education. We also find that household income and parent's educational level are associated with higher demand for at-school online education, while mothers working full-time and fathers in non-regular contracts decreased this demand temporarily. Highlights: We analyzed a panel dataset collected in May and December 2020 in Japan. We examined at-school and outside-school online educational experience. Children with privileged family backgrounds received more online education. Pandemic increased online education use outside school for advantaged children. Parental backgrounds and work styles influence at-school online education demand.